Between Hospitality and Hostility: The Experience of Migration Through Things - Zborowska, Agata (Journal of intercultural studies, 2022)
In this article, I propose the category of 'hospitable things', and argue that it can improve our understanding of the relationships between subjects and objects in the situation of migration. The analysis uses a case study of Polish migration to territories of pre-war Germany and the Free City of Danzig - the so-called Recovered Territories [Ziemie Odzyskane] - in the twilight of World War II. Based on primary sources from the time, I scrutinise how the new Polish settlers transformed German property into 'hospitable things' with substantial help from the post-war propaganda. I reconstruct the affective atmosphere of the period and confront these expectations with the actual experience of hostility materialised by everyday things. The image of 'hospitable things' - waiting and ready to be taken - has been formed through the experience of migration in radically inhospitable circumstances. 'Hospitable things' enable people to cope with the emotions accompanying the fragile experience of displacement; they help to form and transform fears and insecurities, but also desires and wants.